IN VITRO CONSERVATION OF COCONUT ( Cocos nucifera L.) EMBRYOSIN CULTURE MEDIA - SUKENDAH; L. O. CEDO (Biotropia: The Southeast Asian Journal of Tropical Biology, 2005)
The possibility of delaying the germination of mature coconut embryos in vitro for medium-term conservation of coconut was investigated. Embryos of coconut was stored in sugar free, full-strength and half-strength MS media for 3 months with minimal lo ss in viability. Germinability of embryos decreased with prolonged storage. At the end of 9-month storage period, embryos kept in full-strength media were all non-germinable, while those stored in half-stre ngth media still gave 15% germination. Addition of mannitol up to 0.3M did show any significant effect on germination of embryos stored for 3 months. However, longer period of storage helps to a certain extent in the preservation of embryo viability. The presence of mannitol in the storage medium also induced morphological abnormalities in seedlings derived subsequently from the stored embryos. Mannitol at 0.4M was totally deleterious to the embryo. Significance of these findings on coconut gene tic resources conservation are discussed.